Insurance Retreat in Residential Properties from Future Sea Level Rise in Aotearoa New Zealand - Belinda Storey; Sally Owen; Christian Zammit; Ilan Noy (Center for Economic Studies and ifo Institute (CESifo), 2022)
How will the increased frequency of coastal inundation events induced by sea level rise impact residential insurance premiums, and when would insurance contracts be withdrawn? We model the contribution of localised sea level rise to the increased frequency of coastal inundation events. Examining four Aotearoa New Zealand cities, we combine historical tide-gauge extremes with geo-located property data to estimate the annual expected loss from this hazard, for each property, to establish when insurance retreat is likely to occur. We find that as sea level rise changes the frequency of inundation events, 99% of properties currently within 1% AEP coastal inundation zones can expect at least partial insurance retreat within a decade (associated with less than 10cm of sea level rise). Our modelling predicts that full insurance retreat is likely within 20 – 25 years, with timing dependent on the tidal range in each location, and, more intuitively, on the property's elevation and distance from the coast.
Keywords: Q54; R38; 330; insurance; retreat; sea level rise; SLR; climate change